Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1164/arrd.1986.134.5.983
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Kinetics in Stable Atopic Asthmatic Patients1,2

Abstract: The kinetics of platelets labeled with indium-111 were investigated in 13 healthy subjects as well as in 9 patients in the asymptomatic interattack stage of asthma. The survival times of platelets in healthy subjects was 8.9 +/- 1 days; in asthmatic subjects it was 4.7 +/- 1.3 days (p less than 0.001). The survival curve is of a biexponential form in asthmatics, thus suggesting the presence of 2 populations: one with a short life span (23 +/- 7 h), representing a third of the total population (33 +/- 9%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 5 publications
2
23
1
Order By: Relevance
“…Traietti et al [19] reported that the frequency of activated platelets in blood smears from asthma patients was increased in arterial as compared with venous blood, implying activation during transit through the asthmatic lung. In agreement with their observations, Taytard et al [20] noted a reduced survival of a proportion of the population of radiolabelled platelets in asthma pa tients, and platelet counts in peripheral blood have been observed to fall during the reaction to inhaled al lergen [21], Yet again, the clinical observations have been contested; Ind et al [22] failed to find any evi dence that radioactively labelled platelets accumu lated within the lung or that platelet destruction was accelerated following exposure of asthma patients to allergen.…”
Section: Platelets In Asthmasupporting
confidence: 90%
“…Traietti et al [19] reported that the frequency of activated platelets in blood smears from asthma patients was increased in arterial as compared with venous blood, implying activation during transit through the asthmatic lung. In agreement with their observations, Taytard et al [20] noted a reduced survival of a proportion of the population of radiolabelled platelets in asthma pa tients, and platelet counts in peripheral blood have been observed to fall during the reaction to inhaled al lergen [21], Yet again, the clinical observations have been contested; Ind et al [22] failed to find any evi dence that radioactively labelled platelets accumu lated within the lung or that platelet destruction was accelerated following exposure of asthma patients to allergen.…”
Section: Platelets In Asthmasupporting
confidence: 90%
“…The platelet survival curve (radioactivity degradation) showed a biexponential decay pattern, whereas in normal subjects, the curve was monoexponential, suggesting the presence of two highly distinctive populations: one of a short life span (rapidly degrading population) and another of a normal life span. These results suggest the presence of functional or anatomic lesions of platelets in asthmatic patients [23].…”
mentioning
confidence: 60%
“…According to Taytard et al [60], a portion of the platelet population in asthmatics has a significantly reduced survival time. Recent observations also suggest a persistent, partial thrombocytopenia in allergen challenged asthmatics [61], a feature that is particularly evident in asthmatics exhibiting a late asthmatic response (LAR) 3 to 8 hours after Dermatophagoides pteronyssinus challenge [62].…”
Section: Clinical Evidence For a Role Of Platelets In Asthmamentioning
confidence: 99%